Message from the Chief Editor: JTET June 2018 - Editor, Chief (Journal of Technical Education and Training, 2018)
Message from the Chief Editor: JTET June 2018To all our Journalâ€™s readers and followers, a warm welcome to the June issue of 2018. A warm welcome also goes to our new editorial board member, Dr Vidmantas TÅ«tlys from Institute of Education Science of Vytautas Magnus University in Kaunas, Lithuania. In this issue nine papers are shared, presenting TVET practices from diverse geographical locations. The first paper by Chamadia and Shahid from Pakistan reports on an investigation into the outcome of a national level TVET reforms in their country. They identify areas for concern and suggest future actions for more successful TVET reforms.  The second paper by Mason, Mbambo and Pillay reports on the attempt made to understand the poor acceptance of TVET by the public in South-Africa. They focus specifically on the service quality offered by TVET colleges across demographic variables. Their findings support the consistency of perceived service quality irrespective of recipientsâ€™ demographic background. The third paper by Reys-Nickel and Lasonen from the USA discusses student-related and institutional related variables that may influence TVET programmes success rate. Their study can serve as a starting point for other researchers interested in effecting engineering and engineering technologies training outcomes. In the fourth paper by Nwineh and Okwelle from Nigeria, they compare the efficacy of two approaches that can be used to enhance practical skills in domestic electrical installation, a computer simulation and a demonstration approach. Their finding can give guidance to others interested in enhancing studentsâ€™ hands-on skills.In the fifth paper by Techanamurthy, Alias and Dewitt, they share their research findings on the strategies often used by culinary arts students in problem solving; useful information for designing future skills development programmes in the hospitality sector. Continuing with studentsâ€™ skills and competence, Abdullah,  Hussin, Shonubi,  Ghazali, and Abu Talib share in the sixth paper their research on the relationships between studentsâ€™ career decision-making competence, self-knowledge and occupational explorations.  In the seventh paper by Abd Samad et al., they propose the elements that constitute behavioural competency and employability skills of a TVET graduate, the knowledge that can be useful in meeting training and assessment needs of the future.In the eighth paper, the authors discuss an extremely important issue to TVET namely, authentic assessment. Specifically, the authors of this paper, Sutarto and Jaedun present data on the current level of Indonesian TVET teachersâ€™ competence in authentic assessment which they found to be lacking, and to be addressed through appropriate future training suggestions.   Last but not least, we conclude this issue with a timely review paper authored by Chinedu, Wan Mohamed and Ajah which pertains to the provisions, issues and challenges in providing education for sustainable development. Their analysis and synthesis lead to recommendations for teacher training programmes towards enhancing the capability of teachers in providing effective education for sustainable development. With that, I would like to thank all authors, reviewers and editors for making this issue possible.  Please continue to support us for publications of future issues. Professor Dr. Maizam AliasChief Editor